PENGARUH BAURAN PEMASARAN TERHADAP PERILAKU KONSUMEN PADA PEMBELIAN SAYUR DI PASAR MODERN JUMBO MART DELIMA DI KECAMATAN TAMPAN KOTA PEKANBARU - USWATUN KHASANAH, USWATUN KHASANAH; Kusumawaty, Yeni; Eliza, Eliza (Universitas Jambi, 2023)
Â Modern markets are those that are managed in a more modern manner. Modern market management necessitates a competent marketing mix in order to disseminate information, offer goods and services, encourage consumers to buy, and even establish personal preferences for a product's image. Tampan District contains 140 modern marketplaces, including the Modern Jumbo Mart Delima market, which sells a variety of community needs, including the most comprehensive sort of vegetables. The study objectives are as follows: 1) Understanding consumer perceptions of the marketing mix 2) Examining the impact of the marketing mix of product, price, location, service, and promotion on consumer behavior. This study was conducted at the Jumbo Mart Delima Modern Market in Pekanbaru City's Tampan DistrictPurposive sampling was used to identify respondents, with the criterion that customers be 17 years old and have shopped at least twice. In this study, descriptive analysis and multiple linear regression analysis were employed to analyze the data. According to the findings of this study, product, price, location, and service all have a substantial impact on consumer behavior, while service has no impact.